P687 Development of a panel of microbial markers to distinguish transient from pathological dysbiosis. (27th May 2021) - Oliver, L; Ramió-Pujol, S; Malagón, M; Serrano, M; Bahí, A; Busquets, D; Torrealba, L; Serra-Pagès, M; Aldeguer, X; Garcia-Gil, J
Abstract: Background: Dysbiosis is a widely used but unspecific term. It has been defined as any change in the composition of resident microbial communities relative to the ones found in healthy individuals. But it is still unclear which are the appropriate communities to define it and the reference values to measure it. Different studies have described dysbiosis in various diseases such as Inflammatory Bowel Disease (IBD), diabetes, rheumatoid arthritis, and autism, among others. Besides, the microbiota can be altered by transient factors such as antibiotics, diet, stress, or infections. Therefore, different degrees of severity can be associated with the term dysbiosis from which pathological and transient dysbiosis can be differentiated. This work aimed at defining more specifically the term intestinal dysbiosis and to differentiate both transient and pathological dysbiosis. Methods: Fifteen key microbial markers belonging to the principal families, classes and orders found in the human intestinal microbiota were accurately selected based on its functionality: F. prausnitzii (Fpra), E. coli (Eco), Firmicutes (Fir), Bacteroidetes (Bac), A. muciniphila (Akk), Ruminococcus sp. (Rum), Roseburia sp. (Ros), Gammaproteobacteria (Gam), Clostridia cluster I (Clo), Clostridia cluster XIV (XIV), Enterococcus sp., Lactobacillus sp. (Lac), C. albicans (Can), M. smithii (Msm), and the total bacterial load (Eub). The dysbiosis was defined using stool samples in a cohort of healthy subjects (n=24) and then validated with 9 patients diagnosed with intestinal diseases 4 IBD and 2 Irritable Bowel Syndrome (IBS)). Total DNA was extracted and the abundance of microbial markers was analysed by qPCR. Together with the establishment of the most common range in which each microbial marker was found, an index to define the pathological dysbiosis was calculated. Results: Almost all healthy subjects analysed presented one or two slightly altered markers. The affected microbial markers in this "transient dysbiosis" were Fpra, Akk, and Ros, which are indicative of the mucous layer state, Firm as indicative of the lifestyle and fiber intake, Gam as characteristic of the pro-inflammatory state of the gut, and Msm as an altered intestinal habit and gas production. All patients analyzed (IBD and IBS) presented alterations mainly of the bacteria inhabiting the mucosa and an alteration of the opportunistic species related to the disrupted mucous layer and defining "pathological dysbiosis". Conclusion: This study establishes an appropriate abundance range of key microbial markers in the gut, leading to a specific definition of dysbiosis which allows to differentiate the pathological from the transient dysbiosis. These results need further validation in a larger patient cohort.